Consumers' awareness and willingness to purchase organic rice: a case study in Jasin, Melaka / Nur Nadirah Razman - Razman, Nur Nadirah (Faculty of Plantation and Agrotechnology, 2016)
This study seeks to understand the level of awareness, the intention and willingness of purchasing organic rice in Jasin, Melaka population area. This study was carried out by distribute the questionnaire randomly to the Jasin population based on sample size. Data were analyzed using descriptive, correlation and regression analysis to determine relationship between awareness and intention toward willingness. The result showed 31.51% of respondents have received information about organic rice. Correlation and regression analysis stated there was significant relationship for intention, but awareness no significant in regression analysis. This indicates that awareness does not necessarily affect the willingness of purchasing organic rice. Thus, understanding willingness concept will contribute in expanding market of organic rice. Thus, these study can be used in future to encourage people consume organic rice.